Implementasi Kebijakan Gerakan Literasi Digital Dalam Meningkatkan Adaptasi Teknologi Di SMK Assalam Kecamatan Bantur Kabupaten Malang - Octaviani, Cindy Charissa; Prathama, Ananta (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2023)
The government through Minister of Education and Culture Regulation No. 23/2015 on Cultivating Budi Pekerti has established a School Literacy Movement (GLS) policy that includes digital literacy skills. This effort was made by the government to produce a young generation that is technologically proficient with the digital literacy movement in the school environment. In this research, the author wants to know the implementation of the digital literacy movement policy at SMK Assalam in Bantur sub-district. This research uses a qualitative descriptive method by analyzing and summarizing various data obtained through observations and interviews with factual conditions in the field. The results of the study show that the implementation of the digital literacy movement at SMK Assalam has been good so far. The success in its implementation is influenced by good communication between implementers and the openness of implementers in receiving new information. In addition, the school also has adequate infrastructure to support the success of digital literacy. Uneven internet access causes low awareness of students and guardians about the importance of technological skills in the world of education.